Genetic optimal shape design of thin axisymmetric shells and axisymmetric structures - Marcelin, Jean Luc (Computer Assisted Methods in Engineering and Science, 2007)
This work gives some applications of genetic algorithms for shape optimization of thin axisymmetric shells and axisymmetric structures. Calculations are relatively fast for thin axisymmetric shells. For general axisymmetric structures, the concept of mobile or fixed substructures is used and associated to an automatic mesh generator, so calculations are also relatively fast for axisymmetric structures. The limitations or the optimization constraints are included in the chromosomes coding. Three applications are presented; the first one deals with the optimization of the shape of a drop of water, the second one deals with the optimization of the shape of a bottle, and the third one deals with the optimization of the shape of a hydraulic hammer's rear bearing.